QUICK ASSESSMENT METHOD FOR CANISTER STRUCTURAL DESIGN OF INA-CBT - Mulyo Harris Pradono (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
Canister in the Ina-CBT (Indonesian Cable-Based Tsunameter) system is a structure to protect underwater sensor system. Canister and sensor system form the OBU (Ocean Bottom Unit) system. This OBU is connected by land via submarine cable. This canister is used to protect the sensor system from the underwater leakage and water pressure. Because the location of the OBU can usually reach a depth of thousands of meters in the sea, the water pressure on the OBU becomes very large. As an illustration, for a depth of 1000 meters, the pressure on the canister wall is 1 ton per square meter. For this reason, a strong canister structure is needed to withstand water pressure without damage. The strength of this structure can be analyzed using a structural analysis program. However, if a change in pressure and dimension is needed, it needs to be re-modeled to determine its strength which requires time. Therefore a study of a method to determine quickly the strength of the canister is carried out. The results show that this method is very useful to quickly determine the dimensions and initial weight of the canister due to the external pressure load of sea water. For example, with SS 316 L stainless steel material and a canister inner radius of 100 mm, the canister is suitable for further design only for external pressures up to 30 MPa. For pressures above 30 MPa, the thickness and weight of the canisters are becoming impractical for onboard handling. Keywords: canister, ina-cbt, strength, water pressure, quick method.